1993
DOI: 10.1093/occmed/43.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10-week exercise intervention programme on exercise and work capacities in Belfast's ambulancemen

Abstract: The objective of the present study was to investigate the occupational benefits of an exercise intervention programme, including changes in physical working capacity and other physical fitness measures on a group of Belfast ambulancemen. Physical training was performed twice weekly for 10 weeks and consisted primarily of indoor soccer and circuit-training sessions. Both experimental (n = 8) and control subjects (n = 6) were assessed for height (HT), weight (WT), body composition (percentage fat), standing broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 0 publications
1
21
1
1
Order By: Relevance
“…Similarly, Oden et al 27 reported an 8% reduction in body fat among 45 blue-collar workers who participated in a 24-week employee fitness/walking program. Conversely, it should be noted that the findings of two other studies contradict ours; 28,29 however, it is worth mentioning that both studies had a very small number of subjects included in the analysis (35 and 14, respectively, compared with 73 of ours), suggesting that they may have been statistically underpowered to detect a meaningful difference in BMI or body weight/fat.…”
Section: Discussioncontrasting
confidence: 63%
“…Similarly, Oden et al 27 reported an 8% reduction in body fat among 45 blue-collar workers who participated in a 24-week employee fitness/walking program. Conversely, it should be noted that the findings of two other studies contradict ours; 28,29 however, it is worth mentioning that both studies had a very small number of subjects included in the analysis (35 and 14, respectively, compared with 73 of ours), suggesting that they may have been statistically underpowered to detect a meaningful difference in BMI or body weight/fat.…”
Section: Discussioncontrasting
confidence: 63%
“…2004), 10 hafta süreyle haftada iki kez uygulanan dairesel antrenmanda, çalışılan on egzersizden dokuzunda maksimal kuvvetin anlamlı derecede artış gösterdiğini bildirmişlerdir (33). Yine, 10 hafta süreyle haftada iki kez uygulanan dairesel antrenmanın faydalarının incelendiği bir çalışmada, esneklik, maksimal oksijen tüketimi ve anaerobik eşik değerlerinde anlamlı artışlar bulunmuştur (34).…”
Section: Discussionunclassified
“…The study design of the included studies contained four RCTs (Arnetz et al 2009;Elliot et al 2007;Sperlich et al 2009, Kraemer et al 2004, one controlled trial (Knapik et al 2009), one retrospective cohort analysis (Eick et al 2009) and one study with a pre-post design (Gamble et al 1993). The search strategy included studies with a broad scope for work functioning.…”
Section: Cardiovascular Aspectsmentioning
confidence: 99%
“…The exercise intervention programme for ambulance personnel was partly effective (Gamble et al 1993) and respiratory muscle training for military personnel turned out to be not effective (Sperlich et al 2009). Elliot et al (2007) described the promotion of a healthy lifestyle in fire fighters, comparing two different strategies to a control group: a team-centred curriculum and an individual motivational interviewing strategy.…”
Section: Physical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation